Pay for performance: will dentistry follow? - Gilbert Gregg H; Barasch Andrei; Rindal Donald B; Fellows Jeffrey L; Voinea-Griffin Andreea; Safford Monika M (BMC, 2010)
Abstract Background "Pay for performance" is an incentive system that has been gaining acceptance in medicine and is currently being considered for implementation in dentistry. However, it remains unclear whether pay for performance can effect significant and lasting changes in provider behavior and quality of care. Provider acceptance will likely increase if pay for performance programs reward true quality. Therefore, we adopted a quality-oriented approach in reviewing those factors which could influence whether it will be embraced by the dental profession. Discussion The factors contributing to the adoption of value-based purchasing were categorized according to the Donabedian quality of care framework. We identified the dental insurance market, the dental profession position, the organization of dental practice, and the dental patient involvement as structural factors influencing the way dental care is practiced and paid for. After considering variations in dental care and the early stage of development for evidence-based dentistry, the scarcity of outcome indicators, lack of clinical markers, inconsistent use of diagnostic codes and scarcity of electronic dental records, we concluded that, for pay for performance programs to be successfully implemented in dentistry, the dental profession and health services researchers should: 1) expand the knowledge base; 2) increase considerably evidence-based clinical guidelines; and 3) create evidence-based performance measures tied to existing clinical practice guidelines. Summary In this paper, we explored factors that would influence the adoption of value-based purchasing programs in dentistry. Although none of these factors were essential deterrents for the implementation of pay for performance programs in medicine, the aggregate seems to indicate that significant changes are needed before this type of program could be considered a realistic option in dentistry.